Comprehensive analysis of the prognostic impact and immune implication of KIAA1429 in lung adenocarcinoma. Issue 4 (16th December 2022) - Guo, Lei; Huai, Qilin; Zhou, Bolun; Ying, Jianming; Guo, Wei
Abstract: Background: Lung adenocarcinoma (LUAD) is the most common lung cancer worldwide. N6‐methyladenosine (m6A) methylation is a messenger RNA (mRNA) modification that plays a key role in tumor growth, immune microenvironment, and immunotherapy response. This study investigated the expression level, mutation status, prognostic value, and predictive ability for response to anti‐PD‐1 immunotherapy of the m6A methyltransferase KIAA1429 in LUAD. Methods: This study examined multiple public data cohorts and independent samples from National Cancer Center (NCC) to evaluate the clinical significance and prognostic value of KIAA1429 in LUAD using bioinformatics techniques and immunohistochemical staining. We also evaluated the predictive value of KIAA1429 expression for anti‐PD‐1 immunotherapy efficacy. GSEA analysis was performed using KIAA1429 RNA‐seq data at the tumor tissue level and cellular level to explore the potential molecular mechanism. Results: In public databases, KIAA1429 was significantly associated with clinicopathological parameters in LUAD patients and had the potential to predict patient prognosis. The mutation characteristics of KIAA1429‐related genes were analyzed and TP53, TTN, CSMD3, and other genes showed high mutation frequencies in LUAD. An independent cohort of 415 samples confirmed that high KIAA1429 expression was significantly associated with poorer prognosis in LUAD patients. Analysis of a small immunotherapy cohort showed that patients with high expression of KIAA1429 had better response after immunotherapy, and the proportion of patients with immunotherapy response was higher in this group. Conclusions: Our study confirmed that KIAA1429 was highly expressed in LUAD and was significantly associated with poor prognosis. Moreover, KIAA1429 may serve as a potential marker to predict the efficacy of immunotherapy in LUAD. Abstract : KIAA1429, an important "writer" of m6A methylation modification, is not only significantly highly expressed in Lung adenocarcinoma (LUAD) but also significantly associated with poor prognosis of LUAD patients. The small sample immunotherapy cohort analysis showed that patients with high expression of KIAA1429 had better response after immunotherapy, and the proportion of immunotherapy response was higher. KIAA1429 is a potential biomarker for predicting prognosis and efficacy of immunotherapy in LUAD patients.